1996
DOI: 10.1002/chin.199648214
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Potential Antimelanomic Drugs. Part 1. Synthesis and Antimelanomic Effect of a Spin Labelled D,L‐Amino Acid Containing a 2‐ Chloroethylnitrosocarbamoyl Group.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Most of the D,L-amino acid hybrid peptides were found in antibiotic peptides 68,69 and antimicrobial peptides. 70,71 They involve in inactivation of membrane proteins, 72 suppression of human prostate tumour growth, 73 potential anti-melanomic drugs, 74 cell-penetrating, 75 inhibited T-cell activation, 76 or for an immunosensor. 77 In the self-assembling peptide system we used the hybrid peptides with identical sequences.…”
Section: Dl-amino Acid Hybrid Peptide Systemmentioning
confidence: 99%
“…Most of the D,L-amino acid hybrid peptides were found in antibiotic peptides 68,69 and antimicrobial peptides. 70,71 They involve in inactivation of membrane proteins, 72 suppression of human prostate tumour growth, 73 potential anti-melanomic drugs, 74 cell-penetrating, 75 inhibited T-cell activation, 76 or for an immunosensor. 77 In the self-assembling peptide system we used the hybrid peptides with identical sequences.…”
Section: Dl-amino Acid Hybrid Peptide Systemmentioning
confidence: 99%
“…The sensivity of tumours toward chemotherapic drugs varies widely in function of their biochemical characteristics, especially with regards to the metabolism of nucleic acids and the activity of the cell enzymatic equipment [ 1 , 2 ]. Among the chemotherapic agents used in the treatment of some malignant tumours the N -mustards are particularly important [ 3 , 4 , 5 , 6 ]. The cytostatic action of these compounds is exerted by the blocking alkylating effect on the components involved in the anarchic growth of the cancerous cells.…”
Section: Introductionmentioning
confidence: 99%
“…Aminoacids and their derivatives are known to participate in animal metabolism decreasing the toxicity of some drug substances and facilitating the chemotherapic activity [ 4 , 6 , 9 , 11 , 12 , 13 , 14 ]. Based on these considerations the present study is aimed to synthesize new N -mustards with the di-( β -chloro-ethyl)amino group supported by acylated derivatives of N -( meta -aminobenzoyl)- D,L -asparagic acid, N -( meta -aminobenzoyl)- D,L -asparagine and N -( meta -aminobenzoyl)- D,L -methionine, in order to follow their antitumour action by antagonist and alkylating effect.…”
Section: Introductionmentioning
confidence: 99%
“…Following this finding, we have synthesised a number of spin-labelled analogues of the anticancer drug 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosourea (CCNU). Some of these compounds showed advantages over CCNU, by having lower toxicity and higher anticancer activity against some experimental tumour models [11]- [14]. Using the EPR method we had shown that spin-labelled nitrosoureas could scavenge 2 O − ⋅ and thus exhibited high superoxide scavenging activity (SSA) [15].…”
Section: Introductionmentioning
confidence: 99%